2020
DOI: 10.1111/1753-0407.13092
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and risk of dementia in patients with new‐onset type 2 diabetes: A nationwide population‐based cohort study

Abstract: Background: This study examined the relationship between sleep disorders and the risk of dementia in patients with newly diagnosed type 2 diabetes. Methods: This study used the Korean Health Screening Cohort data and included 39 135 subjects aged ≥40 years with new-onset type 2 diabetes between 2004 and 2007, with follow-up throughout 2013. Sleep disorders were measured by F51(sleep disorders not due to a substance or known physiological condition) or G47(sleep disorders) under International Classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The study among the Korean community found that sleep disorders among patients with type 2 diabetes increase the risk of dementia compared to those without sleep disorders (Jin & Choi, 2021).…”
Section: Open Access | Research Notes Issn: 2576-828xmentioning
confidence: 99%
See 1 more Smart Citation
“…The study among the Korean community found that sleep disorders among patients with type 2 diabetes increase the risk of dementia compared to those without sleep disorders (Jin & Choi, 2021).…”
Section: Open Access | Research Notes Issn: 2576-828xmentioning
confidence: 99%
“…Seven different self-report questionnaires, including Auckland Sleep Questionnaire (ASQ), Global Sleep Assessment Questionnaire (GSAQ), Holland Sleep Disorders Questionnaire (HSDQ), Iowa Sleep Disturbances Inventory (ISDI), Sleep Disorders Questionnaire (SDQ), SLEEP-50, and Sleep Symptom Checklist (SSC) of sleep disorders, reported that to compare with other measurements only GCAQ is feasible to use in the general population at the primary care level, with a suggestion of some further development (Klingman et al, 2017). Moreover, sleep disorders among Korean samples were measured by non-organic and organic sleep disorders according to the International Classification of Diseases, Tenth Edition (ICD-10) (Jin & Choi, 2021). In the study of the general population of Finland, insomnia and sleep habits were measured by the International Classification of Sleep Disorders (ICSD) (Ohayon & Partinen, 2002).…”
Section: Open Access | Research Notes Issn: 2576-828xmentioning
confidence: 99%
“…Insomnia increases exposure to many risks, including obesity, [40] type 2 diabetes, [40] cardiovascular disease [41] and even an increased risk of suicide. [42] Notably, poor sleep quality is a much stronger predictor of future health problems than short sleep duration.…”
Section: Introductionmentioning
confidence: 99%